Perancangan Gedung Hotel 4 Lantai di Daerah Solo Baru Sukoharjo Dengan Sistem Rangka Pemikul Momen Biasa - Nugroho, Yusuf Adhitya; , Ir. Ali Asroni, MT (2016)
Solo Baru is one of the areas that are in Grogol, Sukoharjo district developed as one of the economic centers in Sukoharjo so many newcomers perform economic activities, from the high of migrants into Solo Baru led to high demand for lodging. The hotel replied height migrants with good facilities. This final project aims to produce a 4 storey hotel with bearer ordinary moment frame system (SRPMB). Planning this 4-storey hotel uses rules (SNI) SNI 2847-2013 (Requirements for Structural Concrete Building) and ISO 1726-2012 (Planning Procedures for Earthquake Resistance for Building Structure and Non-Building). Planning a 4th floor hotel include beams, columns, plates, foundations and sloof. 4-storey hotel is planned on the site classification of hard soil (SC) with the response modification factor (R) = 3 and the primacy of the building factor Ie = 1.0. Quality of the concrete used is f'c = 25 MPa, then longitudinal reinforcement fy = 350 MPa and shear (begel) fyt = 320 MPa. The tools used to plan, among others SAP2000 program for structural analysis calculations and AutoCad program to plot the shape and detail of the building structure. 4-storey hotel planning results using roof plate thickness of 10 cm and 12 cm thick slab, measuring 250/350 mm joists and girders measuring 400/600 mm and 400/500 mm sized columns. Under the structure of the foundation soles of continuous use with a depth of -2.00 m and the soil bearing capacity = 125 kPa with thick foundation size of 0.35 m and a width of 1.75 m, 2.40 m, 2.50 m, 2.55 m and 3.00 m.